Three-dimensional finite element simulations of various roll's shape during three-roll planetary rolling processes - Wu, Shyue-Jian; Chang, Ming-Hu; Hwang, Yeong-Maw (Computer Assisted Methods in Engineering and Science, 2023)
The purpose of this paper is to analyze the bar rolling process by means of various roll's shapes under the reduction zone of a three-roll planetary mill. The problems were solved with the aid of the finite element program MARC adopting the large deformation-large strain theory and the updated Lagrangian formulation (ULF) and a mesh rezoning procedure was adopted to improve the unexpected error of element turning inside out. The mesh system of the whole bar billet was established by using three-dimensional brick elements, and the three-dimensional elastic-plastic finite element model in MARC was chosen to perform the simulation of the three-roll planetary rolling processes. Totally five different roll's shapes were used to simulate the rolling process. The numerical results; such as the equivalent von Mises stress and plastic strain distributions, rolling force, rolling moment, billet speeds at the entrance and exit planes of the roll gap, etc., are useful in the design of three-roll planetary rolling processes.